Learning Strategies Used by a Member of EDSO in Gaining Speaking Skill Achievement: (A Case Study) - Putri, Parahytha T; Prasetyarini, Aryati, S. Pd, M. Pd (2016)
This research is aimed at describing the learning strategies used by a member of EDSO in gaining speaking skill achievement. This is done by classifying the data taken from the observation and the interview using the theory of learning strategies by Rebecca L Oxford. The type of this research is a case study which belongs to a qualitative research. This research is dealing with an observation and an in-depth interview to the subject to collect the data. The subject of this research is a member of EDSO in Muhammadiyah University of Surakarta. This research's result shows that the subject uses almost all the indirect strategies classified by Oxford in gaining speaking skill achievement. The subject uses 23 indirect strategies; 10 metacognitive strategies, 7 affective strategies, 6 social strategies.